Proyecciones del producto interno bruto PIB e incidencias sobre las variables macroeconómicas en el Ecuador periodo 2008 - 2013 - Del Pezo Gómez, María Angela (2015)
This research work will determine what the impacts and main impact of economic growth in Gross Domestic Product in Ecuador in the periods between 2008 and 2013 were. This is done using the information collected in the following means of primary and secondary information……..